Human–carnivore coexistence in Qomolangma (Mt. Everest) Nature Reserve, China: Patterns and compensation. (May 2016) - Chen, Pengju; Gao, Yufang; Lee, Andy T.L.; Cering, Lhaba; Shi, Kun; Clark, Susan G.
Abstract: Livestock depredation by large carnivores is frequently reported in Qomolangma (Mt. Everest) National Nature Reserve, Tibet Autonomous Region of China. Seeking to minimize conflicts, we assessed depredation patterns and ways to upgrade the compensation program. We gathered 9193 conflict records over 2011–2013 to determine the extent and tempo-spatial patterns of the depredation. We interviewed 22 local officials and 94 residents to learn their views on depredations and to assess the adequacy of compensation. Data showed that wolves ( Canis lupus ), lynx ( Lynx lynx ), and snow leopards ( Panthera uncia ) were the major livestock predators. Total livestock loss accounted for 1.2% of the entire stockholding (n = 846, 707) in the region. Wolves and lynx tended to take sheep and goats, whereas snow leopards favored yaks and cattle in relation to their proportional abundance. Predation mostly occurred in March through July. Livestock depredation by all predators when combined was best explained by terrain ruggedness and density of small- and large-bodied livestock. Temporal and spatial predation patterns varied among carnivores. Most respondents (74%) attributed depredation causes to an increase in carnivore abundance. Only 7% blamed lax livestock herding practice for predation losses. Five percent said that predation was the result of livestock population increases, while 11% had no idea. The compensation scheme was found to be flawed in all aspects—predation verification, application procedure, compensation standard, operational resource allocation, making payment, and other problems. To enhance management for human–carnivore coexistence, we recommend a problem-oriented, integrated, adaptive approach that targets the complex social context of the conflict and addresses the interconnected functions of decision-making process. Highlights: Total livestock depredation losses accounted for 1.2% of the entire stockholding. Wolves, lynx and snow leopards show notable differences in livestock selectivity. Temporal and spatial predation patterns varied among carnivores and livestock. Local people mostly attributed depredation to carnivore population increase. The compensation scheme needs improvement in all aspects of the decision process.